Variety of Phraseology in German Lessons - Khalilova Zilola Farmonovna (Scientific Trends, 2024)
It can be explained from the analysis that the theoretical foundations necessary for the basis of the article are sufficiently provided in European and Russian linguistics, as well as in Uzbek linguistics. The main goal is to "introduce" the description of phraseological units, polysemous and homonymous, descriptive synonymous expressions using this theoretical base to the linguistics of everyday speech, and thereby help to further improve the analytical basis of the phraseological units with the Uzbek language explanation, and the translation system. Phraseologisms can be called unique "language symbols" that contain various information about the happenings. For this reason, everyday speech models expressing the semantic uniqueness of polysemous, homonymous, antonymous, and synonymous expressions are extremely necessary for our national corpus system.
Keywords: Phraseological series, semantically-grammatically, homonymy, synonymy, antonymy, interpretations, separating, semantically, grammatically, expressions, morphological.